A Dimensional Splitting of ETD Schemes for Reaction-Diffusion Systems (Communications in Computational Physics, 2020)
Novel dimensional splitting techniques are developed for ETD Schemeswhich are second-order convergent and highly efficient. By using the ETD-Crank-Nicolsonscheme we show that the proposed techniques can reduce the computationaltime for nonlinear reaction-diffusion systems by up to 70%. Numerical tests are performedto empirically validate the superior performance of the splitting methods.